Cerebrospinal fluid miRNA profile in HIV‐encephalitis1. Issue 5 (28th January 2013) - Pacifici, Marco; Delbue, Serena; Ferrante, Pasquale; Jeansonne, Duane; Kadri, Ferdous; Nelson, Steve; Velasco‐Gonzalez, Cruz; Zabaleta, Jovanny; Peruzzi, Francesca
Abstract: MicroRNAs are short non‐coding RNAs that modulate gene expression by translational repression. Because of their high stability in intracellular as well as extracellular environments, miRNAs have recently emerged as important biomarkers in several human diseases. However, they have not been tested in the cerebrospinal fluid (CSF) of HIV‐1 positive individuals. Here, we present results of a study aimed at determining the feasibility of detecting miRNAs in the CSF of HIV‐infected individuals with and without encephalitis (HIVE). We also evaluated similarities and differences between CSF and brain tissue miRNAs in the same clinical setting. We utilized a high throughput approach of miRNA detection arrays and identified differentially expressed miRNAs in the frontal cortex of three cases each of HIV+, HIVE, and HIV− controls, and CSF of 10 HIV‐positive and 10 HIV‐negative individuals. For the CSF samples, the group of HIV+ individuals contained nine cases of HIV‐associated neurological disorders (HAND) and, among those, four had HIVE. All the HIV‐negative samples had non‐viral acute disseminate encephalomyelitis. A total of 66 miRNAs were found differentially regulated in HIV+ compared to HIV− groups. The greatest difference in miRNA expression was observed when four cases of HIVE were compared to five non‐HIVE cases, previously normalized with the HIV‐negative group. After statistical analyses, 11 miRNAs were fund significantly up‐regulated in HIVE. Although more clinical samples should be examined, this work represents the first report of CSF miRNAs in HIV‐infection and offers the basis for future investigation. J. Cell. Physiol. © 2012 Wiley Periodicals, Inc.